Clinical epidemiological aspects of adults with anterior guide of dysfunctional dental occlusion - Mayelín de la Caridad Suárez González; Silvia María Díaz Gómez; Elisa Amparo Núñez Oduardo; Yoanis Gutiérrez Olives; Omelio Fontaine Machado (Centro Provincial de Información de Ciencias Médicas, 2024)
Introduction: Anterior teeth have a predominant function in the stomatognatic system, essential for the aesthetics, phonation and mastication. Objective: To characterize adults with anterior guide of dysfunctional dental occlusion according to clinical and epidemiological variables. Methods: A descriptive and cross-sectional study, was carried out from October, 2021 to April, 2022, in the 3 de Octubre Teaching Stomatological Clinic from Las Tunas. The universe was formed by 825 medical records that contained the diagnosis of patients with bruxism, traumatic occlusion and temporomandibular disorders who presented anterior guide of the dysfunctional dental occlusion. By means of the intentional non probabilistic sampling, a sample of 615 with entire dental formula or class III partial toothlessness of Kennedy and concluded stomatologic care or inactivation of the cavity and acute inflammatory processes was selected. Results: There was a prevalence of the female sex (54.8%) and the 40-49 age group (33.5%). Bruxism prevailed as clinical diagnosis (41.9%) with prevalence of the corresponding to sleep (39.1%), secondary (51.2%), probable (59.7%) and moderate (69.4%); among the most outstanding classifications was the dysfunctional stomatognatic system (84.4%). The predominant dental clinical manifestations were the wear facets (87.5%). Conclusions: The characterization of patients with anterior guide of the dysfunctional dental occlusion allows to establish an up-to-date panoramic of this health problem, for a better follow-up and treatment to these patients.